Synergistic NaBH4 Reduction/Cyclization of 2‐Aroylcyclopropane‐1‐carboxylates: Synthesis of 3‐Oxabicyclo[3.1.0]hexane Derivatives. Issue 5 (8th February 2017) - Liu, Jiaming; Wang, Lizhong; Qing, Xushun; Zhang, Feixiang; Wang, Ting; Wang, Cunde
Abstract : An NaBH4 reduction/cyclization reaction of readily available 2‐aroyl‐1‐cyano‐3‐arylcyclopropane‐1‐carboxylate compounds was investigated. The process results in the stereoselective synthesis of 3‐oxabicyclo[3.1.0]hexane derivatives in high yields. Abstract : 3‐Oxabicyclo[3.1.0]hexane derivatives were synthesized by a synergistic NaBH4 reduction/cyclization reaction, starting from readily available 2‐aroyl‐1‐cyano‐3‐arylcyclopropane‐1‐carboxylates.